Forord - Brøndsted, Johannes (Jysk Arkæologisk Selskab, 1952)
PrefaceThis photograph shows Dr. Therkel Mathiassen as we Danish archeologists best know him: out in the field, observant, critical, deeply interested, with wrinkles innumerable telling their tale of good humour and intelligence. Mathiassen the omnipresent, the untiring toiler, never sparing himself but always expecting a little more of himself than of others, the quiet, balanced, unhurried worker who nevertheless works at such a phenomenal speed; this is the Mathiassen we know, as we are accustomed to seeing him. What archeological research and the preservation of ancient monuments in Denmark in actual fact owe to him we shall not forget. Let me stress the following two points:In the sphere of research into Denmark's Stone Age Therkel Mathiassen will long be remembered as the great collector and systematizer of new and primary material. Our knowledge of the millenia of Denmark's Mesolithic Period is based to a considerable extent upon the numerous settlement sites and "stations" discovered by Mathiassen in the field and published by him in the literature of the subject. Think only of his work in Aamose or with the Gudenaa siles - not to mention his contributions in the sphere of the New Stone Age or of systematic research into the history of ancient settlement.The other main point is that of preservation of ancient monuments. Since the law protecting these monuments was passed in 1937 no one has laboured remotely comparably with Mathiassen to explain, practise and adapt the provisions of the statute, and in no less degree to fight for actual literal preservation, lest posterity should see the preservation statutes confined to the obscurity of paper, an imaginary life ignored in practice. This battle is still going on, and if a solution is ever found to the problem of an effective watch and ward over Denmark's ancient monuments a large share of the praise for this will be owed to Mathiassen.In the field of Eskimo research Dr. Mathiassen is, as is well known, a figure of international repute, by reason of the work of his youth and early manhood. But the past twenty years of his everactive life he has devoted to a preponderant degree to the excavation of his native soil and to the shrewd and accurate assessment of its fruits. In his department of the National Museum, the former "Oldnordisk Museum", Dr. Mathiassen is a highly respected and beloved chief. Nor could one expect it to be otherwise.Gentle reader, let these lines and the photograph which accompanies them illuminate for you the background and the reason why.Johannes Brøndsted